EFFECT OF SNEAKHEAD FISH SCALE HYDROXYAPATITE AS AN ALTERNATIVE BONE GRAFT MATERIAL ON THE NUMBER OF WISTAR RAT FIBROBLAST - Sulistiawati Sulistiawati; Mellani Cindera Negara; Ulfa Yasmin; Dianita Ellia Prasetya; Michelle Liu; Amanda Siti Triana Putri (Dentino: Jurnal Kedokteran Gigi, 2025)
Background: Bone regeneration is a process to repair bone structure but has limited reparative capacity because the bone resorption process occurs in line with the regeneration process. Bone graft application is required to minimize resorption and guide bone regeneration, including in alveolar bone after tooth extraction. Snakehead fish scales are known to contain hydroxyapatite components as an alternative bone graft material to increase fibroblasts in tooth sockets. Purpose: To determine the effect of sneakhead fish scale hydroxyapatite as an alternative bone graft material on the number of Wistar rat alveolar bone fibroblasts after tooth extraction. Methods: This study was in vivo laboratory experimental study, single blind, with a post test only control group design. The samples used were Wistar rat which were divided into 4 groups after tooth extraction, the treatment group (HAp) was given hydroxyapatite from snakehead fish scales for 7 and 14 days and the control group was given distilled water for 7 and 14 days. Euthanasia of rat was carried out on days 7 and 14, then the jaw was cut off and histopatological preparations were made. The number of fibroblast was counted and analyzed statistically. Results: The Independent T-test showed that the number of fibroblasts was higher in the treatment group than control (p-value>0,05). Conclusion: Hydroxyapatite from snakehead fish scales can significantly increase the number of fibroblasts in rat socket after tooth extraction. Keywords: bone regeneration, fibroblast, snakehead fish scale, tooth extraction, wistar rat